Al2O3 Coated Concentration-Gradient Li[Ni0.73Co0.12Mn0.15]O2 Cathode Material by Freeze Drying for Long-Life Lithium Ion Batteries. (20th August 2015) - Wang, Jingpeng; Du, Chunyu; Yan, Chunqiu; He, Xiaoshu; Song, Bai; Yin, Geping; Zuo, Pengjian; Cheng, Xinqun
Graphical abstract: Highlights: Al2 O3 -coated concentration-gradient oxide is synthesized by a freeze drying method. The effect of Al2 O3 -coating on concentration-gradient cathode is firstly studied. Al2 O3 -coated sample exhibits high capacity and significantly enhanced cyclability. Improved cyclability is ascribed to the effective protection of uniform Al2 O3 layer. Abstract: In order to enhance the electrochemical performance of the high capacity layered oxide cathode with a Ni-rich core and a concentration-gradient shell (NRC-CGS), we use a freeze drying method to coat Al2 O3 layer onto the surface of NRC-CGS Li[Ni0.73 Co0.12 Mn0.15 ]O2 material. The samples are characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, charge-discharge measurements and electrochemical impedance spectroscopy. It is revealed that an amorphous Al2 O3 layer of about 5 nm in thickness is uniformly formed on the surface of NRC-CGS Li[Ni0.73 Co0.12 Mn0.15 ]O2 material by the freeze drying procedure. The freeze drying Al2 O3 -coated (FD-Al2 O3 -coated) sample demonstrates similar discharge capacity and significantly enhanced cycling performances, in comparison to the pristine and conventional heating drying Al2 O3 -coated (HD-Al2 O3 -coated) samples. The capacity decay rate of FD-Al2 O3 -coated Li[Ni0.73 Co0.12 Mn0.15 ]O2 material is 1.7% after 150 cycles at 55 °C, which is 9 and 12 times lower than that of the pristine and HD-Al2 O3 -coated samples. The superior electrochemical stability of the FD-Al2 O3 -coated sample is attributed to the synergistic protection of CGS and high-quality Al2 O3 coating that effectively protect the active material from electrolyte attack. The freeze drying process provides an effective method to prepare the high performance surface-coated electrode materials.